Is day 7 culture necessary for in vitro fertilization of cryopreserved/warmed human oocytes? - Xiangli Niu; Cassie T. Wang; Richard Li; Ghassan Haddad; Weihua Wang (BMC, 2020)
Abstract Background Human embryos are usually cultured to blastocyst stage by Day 5 or 6 after insemination. However, some embryos grow slowly and reach blastocyst stage at Day 7. Acceptable live birth rates have been reported after transfer of Day 7 blastocysts resulted from fresh oocyte in vitro fertilization (IVF). It is unknown whether an extended embryo culture to Day 7 is necessary for cryopreserved oocyte IVF to obtain more transferrable blastocysts. Methods In this study, 455 oocytes from 57 cycles were warmed, inseminated, and the resulting embryos were cultured by Day 7 to examine blastocyst development after extended culture. Fifty one blastocysts from 16 cycles were biopsied to examine embryo aneuploidies. Results It was found that 35.1% of the cycles had Day 7 blastocysts, and 3.5% of the cycles had only Day 7 blastocysts. Day 7 blastocysts accounted for 15.6% of total blastocysts. The proportion of top quality of blastocysts was lower at Day 7 than at Day 5 or 6. However, no differences were observed on aneuploid blastocyst rates among Days 5, 6 and 7. Similar clinical pregnancy, ongoing pregnancy and embryo implantation rates were obtained after Day 7 blastocyst transfer as compared with Day 5 or 6 blastocyst transfer. Conclusion These results indicate that embryos from oocyte warming cycles should be cultured to Day 7 if they do not reach to blastocyst stage by Day 6 so that number of usable blastocysts can be increased.